2010
DOI: 10.3354/cr00911
|View full text |Cite
|
Sign up to set email alerts
|

Bioclimatic envelope model of climate change impacts on blanket peatland distribution in Great Britain

Abstract: Blanket peatlands are rain-fed mires that cover the landscape almost regardless of topography. The geographical extent of this type of peatland is highly sensitive to climate. We applied a global process-based bioclimatic envelope model, PeatStash, to predict the distribution of British blanket peatlands. The model captures the present areal extent (Kappa = 0.77) and is highly sensitive to both temperature and precipitation changes. When the model is run using the UKCIP02 climate projections for the time perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 53 publications
4
94
0
1
Order By: Relevance
“…We therefore used the ratio of actual to equilibrium evapotranspiration (α), which is widely used as an index of plant-available moisture (Prentice et al, 1993), as a surrogate for soil moisture. This index is calculated from the CRU TS3.1 climate data as described in Gallego-Sala et al (2010). Equilibrium evapotranspiration refers to the water loss from a large homogeneous area under constant atmospheric conditions.…”
Section: Environmental Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore used the ratio of actual to equilibrium evapotranspiration (α), which is widely used as an index of plant-available moisture (Prentice et al, 1993), as a surrogate for soil moisture. This index is calculated from the CRU TS3.1 climate data as described in Gallego-Sala et al (2010). Equilibrium evapotranspiration refers to the water loss from a large homogeneous area under constant atmospheric conditions.…”
Section: Environmental Predictor Variablesmentioning
confidence: 99%
“…The availability of remotely sensed data in a number of active fires (Giglio et al, 2006;Bartlein et al, 2008) and burnt areas during the past decade makes it possible now to analyse the controls on wildfire on a global scale Aldersley et al, 2011;Daniau et al, 2012;Moritz et al, 2012;Knorr et al, 2014). Each of these studies considered different sets of potential controls and used different methods.…”
Section: Introductionmentioning
confidence: 99%
“…Bioclimatic modelling results have suggested that the areas suitable for British blanket peatlands may retreat towards the north and west with climate change to the end of the 21 st Century Gallego-Sala et al, 2010). The degradation of peatlands is therefore much more likely in these marginal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gallego-Sala et al (2010) found that temperature tended to be more important than precipitation and moisture index in the variation of the areal extent of the peat bioclimatic envelope through a sensitivity analysis of their PeatStash model.…”
Section: Climatic Drivers Of Changes In Blanket Peat Erosionmentioning
confidence: 99%
“…11.11 Effects of temperature on methane (CH 4 ) efflux from 30 cm diameter Sphagnum papillosum mire cores. Flux measurements were performed in dark conditions (after Daulat and Clymo 1998) bogs in the UK Gallego-Sala et al 2010; Gallego-Sala and Prentice 2013, Fig. 11.12).…”
Section: Climatic Impacts On Biotic Interactionsmentioning
confidence: 99%